(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In India, agricultural productivity has become more reliant on groundwater, resulting in groundwater depletion. Rainfall collecting (RWH) for watershed replenishment is being considered as one solution to the groundwater problem. This may be seen in the increased number of watershed development projects in which RWH is a key architectural component. Understanding the overall impact of these developmental measures is critical for ensuring a beneficial net effect on groundwater both regionally and across a catchment. As a result, the emphasis of this research is on the hydrological impacts of RWH for recharge in rural areas at the micro (individual structure) and regional levels. Surprisingly limited experimental proof of the stated positive impacts at the local level exists, and there are several possible negative consequences at the watershed scale. Field research on the watersheds level is underrepresented, and it is mainly handled via models. Modeling is seen to be an useful method for expanding limited field information, and scenarios analyses might be utilized to assess possible consequences. Many prior RWH modeling studies, on the other hand, either had a narrow focus or were based on insufficient data. In addition to enhancing field data collection, new modeling approaches must be developed. As possible new options, greater use of distant sensors and advanced statistical tools are discussed. In addition, some evaluation criteria are provided for evaluating the hydrological and other consequences of RWH on a local and regional scale as part of drainage improvement.